Effect of Pressure Equalization Groove Structure on Static Characteristics of Aerostatic Bearings - C. Yuanqi; X. Yaping; L. Weining; G. Ning (Journal of Applied Fluid Mechanics)
In order to improve the load capacity and stiffness, the pressure-equalizing groove is introduced into the structure of aerostatic bearing, which can optimize the mechanics characteristics. A Computational Fluid Dynamics (CFD) simulation of bearing with gas-lubricant is developed. The effects of pressure-equalizing groove depth, width, length, number, and supply air pressure on the load capacity, stiffness, and flow rate of orifice-throttle gas bearings are individually analyzed using COMSOL Multiphysics simulation software. The results are then experimentally validated. The results demonstrate that a groove structure designed to equalize pressure can enhance the load-bearing capacity and rigidity of orifice-throttle aerostatic bearings. The static performance of aerostatic bearing increase with the depth, width, number, and supply air pressure of the pressure-equalizing grooves. The peak stiffness of the bearing is significantly enhanced as the depth, width, and supply air pressure of the pressure-equalizing grooves increase. Moreover, the change of grooves number influence the geometric parameter  of the air film associated with the maximum stiffness. Different depths, numbers, and supply air pressures of the pressure-equalizing grooves significantly impact the flow rate. In contrast, the variations in width and length have a minor effect. The numerical simulation findings reveal a 71.67% increase in maximum load-bearing capacity and an 81.20% rise in peak stiffness for gas-floating bearings incorporating pressure-equalizing groove structures. Lastly, the congruence between experimental and simulated stiffness curve variations underscores the validity and robustness of the simulation methodology.